A survey on advanced transmission technologies for high bandwidth and good signal quality for high-speed railways - Abdul Rafay; Sevia Mahdaliza Idrus; Kamaludin Mohamad Yusof; Siti Hasunah Mohammad (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Ahigh-speedrailway (HSR) has gained very high popularity for passengersdue to the fast, reliable, economical and convenient during traveling a verylong-distance journey. Thedemandfor advancedbroadbandservices such aswatching4K movies, cloud computing andonline gaming, has exponentiallyincreased fortravelerson thehigh-speedtrain(HST).The HSTcan’t providegood bandwidth to facilitate these services for travelers via existingtechnologies such as cellular networksand satellite networks because offrequent handoffs, high penetration and fading.So, the bandwidth degradesdramatically due to these issues. Research workers have developed proposalsto handle these problems by advanced transmission technologies for HSR.Until now,varioustransmissionschemeshave beensuggestedby researchworks with thefocusfor either high bandwidth or signal qualityimprovement. This paper presents a survey on advanced transmissiontechnologies for high bandwidth and good signal quality. In this paper, acomprehensive survey of the appropriate literature published that concentrateon advanced transmission methods in HSR communications in getting higherbandwidth efficiency and maximize the signal quality is presented. Advancedtransmission method can be categorized into orthogonal frequencydivisionmultiplexing (OFDM), multiple-input multiple-output (MIMO) and radio-over-fiber (RoF).